Redes francesas de apoyo a los presos políticos y detenidos-desaparecidos uruguayos - Dorothée Chouitem (Centre de Recherches sur les Mondes Américains, 2016)
In the following paper, we will analyze how France dealt with the reports of human rights violations in Uruguay during the 1970s. Most particularly, we are going to focus on the diverse experiences of solidarity with political prisoners, with the National Liberation Movement (“Movimiento de Liberación Nacional-T”) or “Tupamaros” and with the relative members of disappeared Uruguayans. Three case studies will be exemplified : the Defense Committee of Political Prisoners in Uruguay (C.D.P.P.U. 1972), the International Lawyers' Office for the Uruguayan Amnesty (S.I.J.A.U. 1976) and the Association of Family Members of Disappeared Uruguayans (A.F.U.D.E. 1978).